World Suffering and Quality of Life - Anderson, Ronald E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This is the first book tackling the topic of world suffering. It compiles in one place the ideas, perspectives, and findings of researchers from around the world who pioneered research-based understanding of human suffering. Some chapters use the paradigm of ‘quality of life’ to explore ways to enhance knowledge on suffering.  Other chapters show how concepts and knowledge from suffering research can benefit studies on quality of life.      By bringing together in one volume, ideas and research experience from the best minds and leading researchers in the fields of pain, suffering, poverty, deprivation, disability and quality of life (including well-being and happiness), this volume advances social science solutions to a number of major threads of research, most notably suffering. As a whole, the volume advances the fields of suffering and deprivation by suggesting a working typology of suffering and by pointing out the major paradigms for relief of suffering, such as humanitarianism, human rights, caring, and healing. This volume provides a wealth of insights about the interaction between suffering and quality of life, the most up-to-date characterization of worldwide suffering, and a grasp of the implications of these data for local and global policy on health and social well-being. .
Part I World Suffering: A Challenge to Humanity, Humanitarianism and Human Rights -- 1 Implications of World Suffering for Human Progress, Ronald E. Anderson -- 2 Silencing of Sexual Violence against Men in War Torn Countries, Elise Feron -- 3 Social Suffering and Critical Humanitarianism, Iain Wilkinson -- 4 Compassion, Cruelty, and Human Rights, Natan Sznaider -- 5 Making Sense of Suffering: Insights from Buddhism and Critical Social Science, Ruben Flores -- 6 Distant Suffering: The Mediation Of Humanitarian Disaster, Johannes von Engelhardt and Jeroen Jansz -- Part II   Professional and Informal Caregiving -- 1 Suffering and Identity: “Difficult Patients” in Hospice Care, Cindy L. Cain -- 2 Healing Suffering: The Evolution of Caring Practices, Nancy E. Johnston -- 3 Meaning in Bereavement, Robert A. Neimeyer -- 4 Coping with the Suffering of Ambiguous Loss, Pauline Boss -- 5 Social Suffering and an Approach to Professionals’ Burnout, Graciela Tonon, Lía Rodriguez de la Vega, and Inés Aristegui -- 6 The Invisible Suffering of HIV and AIDS Caregivers in Botswana, Gloria Jacques -- 7 Loneliness as Social Suffering: Social Participation, Quality Of Life, and Chronic Stroke, Narelle Warren and Darshini Ayton -- Part III   Quality of Life: Global, Community, and Personal -- 1 Child Well-being and Child Suffering, Kenneth Land, Vicki Lamb, and Qiang Fu -- 2 Felt-Suffering and its Social Variations in China, Yangie Bian and Jing Shen -- 3 Suffering Ailments and Addiction Problems in the Family, Mariano Rojas -- 4 Suffering and Good Society analysis across African countries, Ferdi Botha -- 5 Lifetime Suffering and Capabilities in Chile, Francisca Dussaillant and Pablo Gonzalez -- 6 Shame, Humiliation and Isolation: Missing Dimensions of Poverty Analysis and Suffering, China Mills and Diego Zavaleta -- Part IV   Suffering and Community: Online and offline contexts -- 1 The Cultural Geography of Community Suffering, Daina Cheyenne Harvey -- 2 Social organization of suffering and justice-seeking in a tragic day care fire disaster, Eric C. Jones and Arthur D. Murphy -- 3 Community Quality of Life indicators to avoid tragedies, Rhonda Phillips -- 4 Community Action to Alleviate Suffering from Racism: The Role of Religion and Caring Capital in Small City USA, Meg Wilkes Karraker -- 5 Suffering in Online Interactions, Katrin Döveling & Katrin Wasgien -- 6 Cosmopolitan Perspectives on Suffering, Laura Robinson -- 7 Iconography of Suffering in Social Media: Images of Sitting Girls, Anna Johansson & Hans Sternudd -- Part V   Research and Policy Challenges for the Future -- 1 The Neurosociology of Social Rejection and Suffering, David D. Franks -- 2 Collaborative Humanitarianism: Information Networks that Reduce Suffering, Louis-Marie Ngamassi Tchouakeu and Andrea H. Tapia -- 3 A New Method For Measuring and Analyzing Suffering–Comparing Suffering in Italian Society, Marco Fattore and Filomena Maggino -- 4 The Micropolitics of Suffering, Ara Francis and Daina Cheyenne Harvey -- 5 Emotions, empathy and the choice to alleviate suffering, Caitlin O. Mahoney & Laura M. Harder -- 6 How Suffering Challenges our Future, Ronald E Anderson.
Keywords: Quality of life; Ethics; Social policy; Medical research; Quality of Life Research; Ethics; Social Policy; Quality of Life Research